'I don't want to get in trouble': a study of how adults with intellectual disabilities convert and navigate intellectual disability sexual fields. Issue 9 (3rd August 2022) - Santinele Martino, Alan
Abstract: Drawing on interviews with 46 adults with intellectual disabilities in Ontario, Canada, this article suggests a different starting point in understanding the constraints that limit which sexual fields are available to people with intellectual disabilities. Because of surveillance, infantilisation and control, people with intellectual disabilities sometimes have to claim and convert other spaces such as day programmes, group homes and other residential settings into sexual fields. Without understanding these experiences, we may not recognise these intellectual disability sexual fields as settings for the pursuit of intimacy and love. These are valuable insights that bring into view how some marginalised sexual actors may covert social fields into sexual fields as a means of responding to lack of access to and exclusion from mainstream sexual fields.